Eruptions and Social Media: Communication and Public Outreach About Volcanoes and Volcanic Activity in Italy - Todesco, Micol; De Lucia, Maddalena; Bagnato, Emanuela; Behncke, Boris; Bonforte, Alessandro; De Astis, Gianfilippo; Giammanco, Salvatore; Grassa, Fausto; Neri, Marco; Scarlato, Piergiorgio; Neri, Augusto (Frontiers in Earth Science, 2022)
Italy is the land of iconic volcanoes, whose activity has been witnessed, described and portrayed for centuries. This legacy has greatly contributed to shaping the public perception of volcanoes and their impact, well beyond the national borders. Stories about famous eruptions overlap and nowadays easily mix up with the impressive footage that is readily available from ongoing eruptions worldwide. As a result, the public discourse may flatten the wide spectrum of possible phenomena into an oversimplified sketch of volcanic eruptions and their impact, where all events seem equally probable and look alike. Actual volcanoes differ in size, eruption magnitude, state of activity, eruptive style, geographical position, and each is located within a specific social and cultural context. All these elements combine in defining the consequences of volcanic activity as well as in determining the severity of the damage and the size of the impacted area. How can we convey such a complexity to the general public? Can social media contribute to raise awareness and build a more resilient society? An effective hazard communication should propose a comprehensible yet realistic description of volcanic settings and provide adequate tools to recognize and understand the specific features of each phenomenon and volcanic area. As we write, two Italian volcanoes display persistent eruptive activity, while other two are going through unrest phases that started in 2012, at Campi Flegrei, and in late summer of 2021, at Vulcano Island. Other active volcanoes (Vesuvius, Ischia, Colli Albani, Lipari, and Pantelleria) have been dormant for tens, hundreds, or thousands of years. Communication in these different contexts also require different approaches that take into account the specific needs of local communities. Social media may provide a unique opportunity to quickly share relevant news and information. Yet, this type of communication has its challenges and volcano observatories can rarely rely on expert social media managers. Sharing experiences and lessons learned is a key to ensure the growth of the volcanological community and improve its ability to connect and engage local residents. Here we discuss the online communication strategies implemented by the Istituto Nazionale di Geofisica e Vulcanologia (INGV) since 2018 to inform Internet and social media users about volcanoes, volcanology, and ongoing volcanic activity, both in Italy and abroad. We describe the internal procedures that we developed and practiced and the experience gathered so far, during both quiet periods and a few volcanic crises. Our experience confirms previous indications about the importance of a steady online presence and suggests that public interest is not always easily predictable.